Practical computation of the diffusion MRI signal based on Laplace eigenfunctions: permeable interfaces - Agdestein, Syver Døving; Tran, Try Nguyen; Li, Jing‐Rebecca (NMR in biomedicine, 2022)
The complex transverse water proton magnetization subject to diffusion‐encoding magnetic field gradient pulses in a heterogeneous medium such as brain tissue can be modeled by the Bloch‐Torrey partial differential equation. The spatial integral of the solution of this equation in realistic geometry provides a gold‐standard reference model for the diffusion MRI signal arising from different tissue micro‐structures of interest. A closed form representation of this reference diffusion MRI signal, called matrix formalism, which makes explicit the link between the Laplace eigenvalues and eigenfunctions of the tissue geometry and its diffusion MRI signal, was derived 20 years ago. In addition, once the Laplace eigendecomposition has been computed and saved, the diffusion MRI signal can be calculated for arbitrary diffusion‐encoding sequences and b‐values at negligible additional cost. In a previous publication, we presented a simulation framework that we implemented inside the MATLAB‐based diffusion MRI simulator SpinDoctor that efficiently computes the matrix formalism representation for biological cells subject to impermeable membrane boundary conditions. In this work, we extend our simulation framework to include geometries that contain permeable cell membranes. We describe the new computational techniques that allowed this generalization and we analyze the effects of the magnitude of the permeability coefficient on the eigendecomposition of the diffusion and Bloch‐Torrey operators. This work is another step in bringing advanced mathematical tools and numerical method development to the simulation and modeling of diffusion MRI. We present a method of computing the dMRI signal for permeable interfaces in the MATLAB‐based SpinDoctor toolbox using finite elements. A Laplace eigenfunction basis is computed, independently of the magnetic gradient sequence. The coefficients of the magnetization and resulting dMRI signal in the Laplace basis can be computed quickly for different gradient sequences, with high precision. The eigenmodes are filtered by identifying a range of physical length scales.